Adoption of the principle of autonomy in the promotion of community development practices in Nigeria (2023)
This paper presents autonomy as a principle rooted in ethics - a normative branch of philosophy which applies to most human development activities. Since community development activities continue to grow both in developing and developed countries with its attendant agitations for autonomy, it is proposed that autonomy should be adopted for grassroots development. Autonomy remains an ingredient that can unleash massive human potentials within people and harness local resources in communities in order to promote broad based human sustainable growth and development. The members of various localities ought to be involved in the articulation of their own felt needs and running of their own affairs without inhibiting external assistance. So, external assistance should submit to the overriding interests and aspirations of the people so as to address the difficulties of sustainability in development programmes. This paper proposes autonomy as an ethical value in community engagement.